2014
DOI: 10.1016/j.ymeth.2013.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing conformational dynamics of single P-glycoprotein transporters by Förster resonance energy transfer using hidden Markov models

Abstract: Single-molecule Förster resonance energy (smFRET) transfer has become a powerful tool for observing conformational dynamics of biological macromolecules. Analyzing smFRET time trajectories allows to identify the state transitions occuring on reaction pathways of molecular machines. Previously, we have developed a smFRET approach to monitor movements of the two nucleotide binding domains (NBDs) of P-glycoprotein (Pgp) during ATP hydrolysis driven drug transport in solution. One limitation of this initial work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Accompanying molecular dynamics simulations of the APO and MgATP docked states resulted in only marginal changes of the distance distribution with an increased propensity of closed NBDs after MgATP binding, and overall underlined the highly mobile nature of P-gp. The broad distribution of NBD distances accounting for at least four and possibly up to nine conformational states was also described in single-molecule FRET studies (Verhalen et al, 2012; Zarrabi et al, 2014), which further showed that conformations with closely spaced NBDs are short lived during active MgATP hydrolysis conditions. Overall, although these studies mainly focused on the separation of the NBDs, the data are in line with our whole molecule, single particle EM observations.…”
Section: Discussionmentioning
confidence: 53%
“…Accompanying molecular dynamics simulations of the APO and MgATP docked states resulted in only marginal changes of the distance distribution with an increased propensity of closed NBDs after MgATP binding, and overall underlined the highly mobile nature of P-gp. The broad distribution of NBD distances accounting for at least four and possibly up to nine conformational states was also described in single-molecule FRET studies (Verhalen et al, 2012; Zarrabi et al, 2014), which further showed that conformations with closely spaced NBDs are short lived during active MgATP hydrolysis conditions. Overall, although these studies mainly focused on the separation of the NBDs, the data are in line with our whole molecule, single particle EM observations.…”
Section: Discussionmentioning
confidence: 53%
“…Here we summarize both Information theoretic [181][182][183][184] as well as Bayesian [35,36,147,[185][186][187][188] model selection criteria.…”
Section: Brief Overview Of Model Selectionmentioning
confidence: 99%
“…However, to reveal the simultaneous attachment of both FRET donor and acceptor fluorophores on the individual enzyme, a more sophisticated laser excitation scheme with two alternating wavelengths is recommended. We have established such a confocal setup for duty cycle-optimized alternating laser excitation (DCO-ALEX [71][72][73][74][75][76] ) using pulsed lasers but could not use this microscope for our measurements here. Therefore, low FRET efficiencies of photon bursts with proximity factors 0<P<0.2 might result from FRET donor-only labeled enzymes and should be omitted from further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This approach could also be used for the proteoliposomes measured here, and would improve the detection of fluctuating FRET levels. Furthermore, ambiguities due to manual assignment of FRET levels in the time traces and small smFRET data sets (sufficient for our proof-of-principle study here) have to be solved, for example, using automatic data analysis tools like Hidden Markov Models (HMM) [75,81] .…”
Section: Discussionmentioning
confidence: 99%